Parental perceptions and the 5C psychological antecedents of COVID-19 vaccination during the first month of omicron variant surge: A large-scale cross-sectional survey in Saudi Arabia - Alenezi, Shuliweeh; Alarabi, Mohammed; Al-Eyadhy, Ayman; Aljamaan, Fadi; Elbarazi, Iffat; Saddik, Basema; Alhasan, Khalid; Assiri, Rasha; Bassrawi, Rolan; Alshahrani, Fatimah; Alharbi, Nasser S.; Fayed, Amel; et al. (Frontiers in Pediatrics, 2022)
Background: With the rapid surge of SARS-CoV-2 Omicron variant, we aimed to assess parents’ perceptions of the COVID-19 vaccines and the psychological antecedents of vaccinations during the first month of the Omicron spread. Methods: A national, cross-sectional online survey in Saudi Arabia was conducted (December 20, 2021-January 7, 2022). Convenience sampling was used to invite participants through several social media platforms, including WhatsApp, Twitter, and email lists. We utilized the validated 5C Scale, which evaluates five psychological factors influencing vaccination intention and behavior: confidence, complacency, constraints, calculation, and collective responsibility. Results: Of the 1340 respondents, 61.3% received two doses of the COVID-19 vaccine, while 35% received an additional booster dose. 54% were unwilling to vaccinate their children aged 5-11, and 57.2% were unwilling to give the additional booster vaccine to children aged 12-18. Respondents had higher scores on the construct of collective responsibility, followed by calculation, confidence, complacency, and finally constraints. Confidence in vaccines was associated with willingness to vaccinate children and positively correlated with collective responsibility (p<0.010). Complacency about COVID-19 was associated with unwillingness to vaccinate older children (12-18 years) and with increased constraints and calculation scores (p<0.010). While increasing constraints scores did not correlate with decreased willingness to vaccinate children (p=0.140), they did correlate negatively with confidence and collective responsibility (p<0.010). Conclusions: The findings demonstrate the relationship between the five antecedents of vaccination, the importance of confidence in vaccines, and a sense of collective responsibility in parents’ intention to vaccinate their children. Campaigns addressing constraints and collective responsibility could help influence the public’s vaccination behavior.